2018
DOI: 10.1161/atvbaha.118.310227
|View full text |Cite
|
Sign up to set email alerts
|

Impact of miRNA in Atherosclerosis

Abstract: MicroRNAs (miRNAs) have received most of the attention over the last decades in particular for their role in tempering gene expression. An increasing number of studies highlighting the importance of miRNAs in the development and progression of atherosclerosis have been performed. Recently, it was shown that miRNAs exert their role in the pathophysiology of atherosclerosis via the regulation of atherosclerosis-prone genes as well as their impact in regulating post-transcriptional gene expression. Hence, by affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(120 citation statements)
references
References 133 publications
(179 reference statements)
1
117
1
1
Order By: Relevance
“…Microribonucleic acids (miRNAs), with lengths of 20–24 nucleotides, have been proposed to have the capacity to function in RNA splicing and posttranscriptional regulation of gene expression [ 3 ]. Accumulating evidence suggests that miRNAs are widely involved in the normal functioning of cells, and dysregulation of miRNA is associated with disease [ 4 , 5 ]. Advanced studies showed that miRNAs, including miR-126, let-7e-5p, and miR-120, participated in biological functioning of EPCs [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microribonucleic acids (miRNAs), with lengths of 20–24 nucleotides, have been proposed to have the capacity to function in RNA splicing and posttranscriptional regulation of gene expression [ 3 ]. Accumulating evidence suggests that miRNAs are widely involved in the normal functioning of cells, and dysregulation of miRNA is associated with disease [ 4 , 5 ]. Advanced studies showed that miRNAs, including miR-126, let-7e-5p, and miR-120, participated in biological functioning of EPCs [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the deepening of basic research, increased evidence has indicated that various miRNAs participate in the induction of AS by affecting the transformation of the VSMCs phenotype, thereby playing an important role in regulating AS. Recent studies have shown that miRNAs can be used as potential targets for the treatment of AS, which can also be used to predict the progression of atherosclerotic disease and the occurrence of cardiovascular events (Lu et al, ). Further in‐depth research should be pursued to identify potential molecular targets for atherosclerotic disease and provide novel evidence for the intervention, diagnosis, and treatment of clinical atherosclerotic disease.…”
Section: Resultsmentioning
confidence: 99%
“…MiRNA-126-5p is one of the miRNAs that is specifically expressed in endothelial cells. It can modulate VEGF, acting as a proangiogenic miRNA, [12] and facilitates endothelial cell proliferation and prevents atherosclerotic lesion formation. [13] The knockdown of miR-126 in mice resulted in the loss of vascular integrity and angiogenic activity, and an impaired proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%